Crecimiento de hembras cruzadas en el trópico colombiano - Ramírez, Edison J; Cerón Muñoz, Mario F; Herrera, Ana C; Vergara, Oscar D; Arboleda, Elkin M; Restrepo B, Luis F (Revista Colombiana de Ciencias Pecuarias, 2013)
Summary The aim of this study was to describe the growth of crossbred females of six genetic groups using the model of Brody. Genetic groups evaluated were: 50% Angus 50% Zebu (AZ), 50% BON 50% Zebu (BZ), 100% Zebu (Z), 50% Romosinuano 50% Zebu (RZ), 50%Senepol 25% Angus 25% Zebu (SAZ), and 50% Senepol 50%Zebu (SZ). The percent of maturity at 12, 18, and 24 months and ages at 75% and 95% of maturity was estimated. The maturity at 12 months varied between 42% and 48.5%, at 18 months between 53% and 60%, and at 24 months between 61% and 69%. The genetic group more precocious was AZ, and less precocious was BZ. The age at 75% of maturity varied between 1067 and 1468 days; and age at 95% of maturity varied between 2396 and 3322 days.